Impact of Intranasal Corticosteroids on Intraocular Pressure and Retinal Nerve Fiber Layer Thickness: A Cross-Sectional Study at a Tertiary Care Hospital in Pakistan - Muhammad Salar-e-Azam, Abdullah Naeem Syed, Rehan Moinuddin Shaikh, Dilshad Alam Khan, Sadia Majeed, Abdur Rauf Hammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Intranasal corticosteroids (INCS) are widely prescribed for allergic rhinitis and chronic sinusitis due to their potent local anti-inflammatory action and minimal systemic absorption. However, concerns remain regarding their potential ocular side effects, particularly intraocular pressure (IOP) elevation and retinal nerve fiber layer (RNFL) thinning. Objective: To assess the impact of long-term INCS use on intraocular pressure and retinal nerve fiber layer thickness among adult patients in Pakistan. Methods: This cross-sectional study was conducted at the Civil Hospital Hyderabad (LUMHS) and Al-Shifa Trust Eye Hospital, Rawalpindi, from February 2022 to May 2023. A total of 150 adults were enrolled 75 chronic INCS users (≥3 months) and 75 age- and sex-matched controls. Participants underwent detailed ophthalmic evaluation including visual acuity, slit-lamp examination, Goldmann applanation tonometry, ultrasound pachymetry for central corneal thickness (CCT), and spectral-domain optical coherence tomography (OCT) for RNFL assessment. Data were analyzed using SPSS v26. Results: Mean IOP was significantly higher in INCS users compared to controls (15.3 ± 2.6 mmHg vs. 14.4 ± 2.4 mmHg; p = 0.018). The rise in IOP correlated modestly with duration of INCS use, being greatest in those using INCS for ≥12 months. However, global and quadrant-wise RNFL thickness did not differ significantly between groups (98.4 ± 8.3 µm vs. 99.2 ± 8.0 µm; p = 0.47). No cases of glaucomatous optic changes were observed. Conclusion: Chronic intranasal corticosteroid therapy causes a mild but statistically significant increase in intraocular pressure without structural retinal nerve fiber loss. Periodic IOP monitoring is recommended in long-term users, especially in glaucoma-prone individuals. Keywords: Intranasal corticosteroids, intraocular pressure, retinal nerve fiber layer, glaucoma, allergic rhinitis, Pakistan